Survey of negative selection algorithms - Zhang-zan JIN; Ming-hong LIAO; Gang XIAO (Tongxin xuebao, 2013)
A review of NS was given.Firstly,the basic principle of negative selection algorithm and its history were introduced.Secondly,various negative selection algorithms were grouped into different categories by different criteria and the application of NS was described.Besides,some open problems in the development of NS algorithms were presented and analyzed.Finally,a discussion of future trends was conclued.